Comparison of food and beverage companies’ financial performance on the Indonesian Stock Exchange before and after the COVID-19 pandemic, based on economic value added - Hamdani, Hamdani; Nurwati, Solikah; Mahrita, Ani (JSM: Jurnal Sains Manajemen, 2024)
This study examined variations in the financial performance of food and beverage enterprises before the COVID-19 outbreak in 2018-2019 and during the pandemic in 2020-2021, utilizing the Economic Value Added (EVA) methodology. This study employs a quantitative research design and relies on secondary data sources. The data used in this study were acquired from financial reports of food and beverage companies listed on the Indonesia Stock Exchange from 2018 to 2021. A total of 17 companies were included in the sample. This study employed the Economic Value Added (EVA) approach and utilized SPSS 20.0 software. The findings of this analysis suggest no discernible disparities in the financial performance of food and beverage companies listed on the Indonesia Stock Exchange before and after the COVID-19 outbreak